Child factors associated with complementary feeding practices in Uganda. Issue 1 (2nd January 2017) - Mokori, Alex; Schonfeldt, Hettie; Hendriks, Sheryl L
Abstract : Objectives: The objective of the study was to identify child factors that influenced complementary feeding practices in 2006 and 2011 in Uganda. Design: Trend analysis of Uganda Demographic and Health Surveys (UDHS) from 2006 and 2011. Subjects and setting: Children aged 6 to 23 months, Uganda. Results: Between 2006 and 2011, the percentage of children in Uganda consuming an adequate complementary diet increased by 3.1%. Duration of breastfeeding increased in this time from 11 months to 12 months, with the percentage of mothers who were still breastfeeding their children at two years decreasing from 55.2% to 46.5%. Factors such as child's age, deworming for intestinal parasites and receiving DPT3 and measles vaccines, increased the likelihood of caregivers providing children with a minimum acceptable diet. Children aged 6 to 8 months and 12 to 17 months tended to receive adequate complementary in both 2006 and 2011. Although bottle-feeding was highest among the children aged 6 to 11 months, amongst those reported with a fever, acute respiratory infection (ARI) or diarrhoea, it had no statistically significant effect in either 2006 or 2011. Conclusion: Caregivers who take their children for deworming and DPT3 and measles vaccinations are more likely to feed them adequate diets, especially those aged 6 to 17 months. This is probably due to the mothers' interaction with healthcare practitioners who teach and support complementary feeding. Telling caregivers about complementary feeding practices during immunisation and deworming consultations is likely to encourage beneficial complementary feeding practices in Uganda.